Internalization of Metal–Organic Framework Nanoparticles in Human Vascular Cells: Implications for Cardiovascular Disease Therapy - Dana E. Al-Ansari (16388527) (2020)
Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality worldwide. Alteration of endothelial cells and the underlying vasculature plays a central role in the pathogenesis of various CVDs. The application of nanoscale materials such as nanoparticles in biomedicine has opened new horizons in the treatment of CVDs. We have previously shown that the iron metal–organic framework nanoparticle, Materials Institut Lavoisier-89 (nanoMIL-89) represents a viable vehicle for future drug delivery of pulmonary arterial hypertension. In this study, we have assessed the cellular uptake of nanoMIL-89 in pulmonary artery endothelial and smooth muscle cells using microscopy imaging techniques. We also tested the cellular responses to nanoMIL-89 using molecular and cellular assays. Microscopic images showed cellular internalization of nanoMIL-89, packaging into endocytic vesicles, and passing to daughter cells during mitosis. Moreover, nanoMIL-89 showed anti-inflammatory activity without any significant cytotoxicity. Our results indicate that nanoMIL-89 formulation may offer promising therapeutic opportunities and set forth a new prototype for drug delivery not only in CVDs, but also for other diseases yet incurable, such as diabetes and cancer. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/nano10061028